1999
DOI: 10.1149/1.1391917
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Chemical Vapor Deposited Amorphous Fluorocarbons for Low Dielectric Constant Interlayer Dielectrics

Abstract: C‐F materials, deposited by chemical vapor deposition (CVD) have been studied for their potential use as a low dielectric constant intermetal dielectric material for semiconductor applications. Though a dielectric constant of ∼2.4 has been determined, thermal stability of the material needs to be improved. It is shown that the presence of O and/or OH in the system causes a pyrolytic decomposition of the material causing CO and CO2 to outgas from the material at low temperatures. This causes the C‐F matrix to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
17
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 14 publications
3
17
0
Order By: Relevance
“…Such reactions have been previously described in Refs. [7,53]. These reaction pathways reduce CO and OH bonding, increase crosslinked structure and do not cause extensive breakup of linear CF 2 chains, which is consistent with the XPS and IR absorption results.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Such reactions have been previously described in Refs. [7,53]. These reaction pathways reduce CO and OH bonding, increase crosslinked structure and do not cause extensive breakup of linear CF 2 chains, which is consistent with the XPS and IR absorption results.…”
supporting
confidence: 86%
“…9(b) reaction (e)), to produce (CF 2 ) 2n -C(O)OH and HF during the film growth as shown by reaction (g) in Fig. 9(b) [50,53]. A substantial decrease in OH IR absorption is seen after anneal which remain unaffected after exposure of annealed films to atmospheric moisture.…”
mentioning
confidence: 99%
“…In fact, there has been much investigative work on a-C:F. Ma et al discussed 10 the effect of the deposition temperature on thermal and dielectric constant aspects of a-C:F. Detailed material analyses of a-C:F through x-ray photoelectron spectroscopy ͑XPS͒ and Fourier-transform infrared ͑FTIR͒ spectra have been implemented. 11 Effects of process pressure for the same questions were reported by the Endo groupe. 12 In reviewing most of those investigations, optimization between process parameters and even integral issues with sequential process was lacking.…”
Section: Introductionmentioning
confidence: 73%
“…The fluorine contents are generally present in the fluorocarbon species (CF x ), since these species are the major chemical constituents of a-C:F films and are often observed in TDS spectra, where F, HF is difficult to detect due to the reaction of those gases with Si/SiO 2 in the measurement system, leading to the formation of SiF 4 . 12 On the other hand, charged HF species are required by the TDS approach and only a few of them are formed. In general, a portion of the fluorocarbon species in the a-C:F films, as a terminal group, might react with environmental moisture and form corrosive HF which corrodes metals.…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] Yang et al elucidated the structural evolution of the a-C:F film during thermal annealing. 7 Yokomichi further indicated that the dangling bond density increased after annealing a-C:F films at 400°C.…”
mentioning
confidence: 99%